2000
DOI: 10.1677/joe.0.1650337
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone modulates growth hormone secretion at the hypothalamic but not at the hypophyseal level in the adult male rhesus monkey

Abstract: We investigated a possible modulation of growth hormone (GH) secretion by testosterone by measuring the growth hormone releasing hormone (GHRH)-stimulated and N-methyl-,-aspartic acid (NMA)-induced GH secretion in adult rhesus monkeys. Intact, orchidectomized and testosterone-substituted (testosterone enanthate 125 mg/ week, i.m. for 5 weeks) orchidectomized monkeys (n=5) were used in the study. GHRH (25 µg/kg body weight) or NMA (15 mg/kg body weight) was infused through a Teflon cannula implanted in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Similar results were observed in hypogonadal men after 24 wk of T replacement therapy (250 mg im every 3 wk) (5). As a consequence, other studies (5,34) have suggested that the stimulatory action of T may involve promoting GHRH release from the hypothalamus rather than potentiating its action at the level of the pituitary. In addition, T therapy in healthy older men is known to attenuate feedback inhibition by GH and IGF-I (42).…”
Section: Discussionsupporting
confidence: 67%
“…Similar results were observed in hypogonadal men after 24 wk of T replacement therapy (250 mg im every 3 wk) (5). As a consequence, other studies (5,34) have suggested that the stimulatory action of T may involve promoting GHRH release from the hypothalamus rather than potentiating its action at the level of the pituitary. In addition, T therapy in healthy older men is known to attenuate feedback inhibition by GH and IGF-I (42).…”
Section: Discussionsupporting
confidence: 67%
“…1,[43][44][45] The effect of Te in the human is not sex-limited, because masculinizing doses of Te stimulate the somatotropic axis in the genetically female premenopausal patient undergoing medical-surgical gender reassignment. Te also drives GH and IGF-I secretion in the monkey, cow, sheep and rat.…”
Section: Discussionmentioning
confidence: 99%
“…Te also drives GH and IGF-I secretion in the monkey, cow, sheep and rat. 1,[43][44][45] The effect of Te in the human is not sex-limited, because masculinizing doses of Te stimulate the somatotropic axis in the genetically female premenopausal patient undergoing medical-surgical gender reassignment. 9 In contrast, elevating Te concentrations by up to 8-fold for 1 week did not detectably increase GH secretion and IGF-I concentrations in healthy postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…A cattle reaches its sexual maturity at the age of 12 months old (Djarijah, 2012;Wejdmark, 2014). The androgen on male calves that spur body growth cause bone growth has not increased (Rizvi et al, 2000), so that there is no difference in body length and chest girth. This shows that sex does not affect the body length and chest girth.…”
Section: Body Length and Chest Girthmentioning
confidence: 99%